Construction of single-atom catalysts for electro-, photo- and photoelectro-catalytic applications: State-of-the-art, opportunities, and challenges. (March 2022) - Xia, Jiexiang; Wang, Bin; Di, Jun; Li, Yingjie; Yang, Shi-Ze; Li, Huaming; Guo, Shaojun
Graphical abstract: Abstract: The design and construction of high-performance catalysts can provide excellent opportunities for solving the challenges related to energy conversion and environmental pollution. Single-atom catalysts (SACs) have recently emerged as promising alternatives to commercial catalysts in the fields of photo-/electro-catalysis due to their unique electronic structure. Herein, we present a comprehensive review of significant breakthrough, remaining challenges, and perspectives regarding SACs in terms of catalytic activity, selectivity, and stability. We will first introduce the emergence and development of SACs. Subsequently, the recent advance in the synthesis of SACs with emphasis on available strategies and selected substrates, and corresponding characterization techniques will be summarized. The relationship between the electro-, photo-, and photoelectro-catalytic mechanism and the unique structures and coordination environment of the catalysts will be also discussed. Finally, we will highlight the challenges and opportunities related to SACs in the field of photo/electro-catalysis.